Organisational behaviour: global and Southern African perpectives - Robbins, Stephen P (Cape Town: Pearson Education, 2004)
This book is the first Southern African edition of Stephen P. Robbins's Organizational Behaviour, the best-selling organisational behaviour textbook worldwide.
Keywords: Organizational behaviour -- Southern Africa